2017
DOI: 10.1038/s41598-017-05856-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Effect of lncRNA HOXA11-AS in NSCLC: A Study Based on Bioinformatics, In Vitro and in Vivo Verification

Abstract: HOXA11 antisense RNA (HOXA11-AS) has been shown to be involved in tumorigenesis and development of different cancers. However, the role of HOXA11-AS in non-small cell lung cancer (NSCLC) remains unclear. In this study, we firstly explored and confirmed the expression of HOXA11-AS in NSCLC tissues and cells. Cytometry, CCK-8, cell scratch, migration, Matrigel invasion and flow cytometry assays were performed to determine the biological impact of HOXA11-AS in vitro. Furthermore, a chick embryo chorioallantoic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…Moreover, knockdown of HOXA11‐AS inhibited the proliferation, migration, invasion, tumorigenic as well as the angiogenic capability of NSCLC cells and induced apoptosis. HOXA11‐AS also leads to cell cycle arrest at G0/G1 or G2/M phase 10. In another study, Chen et al concluded that HOXA11‐AS was considerably upregulated in NSCLC tissues, compared with that of normal tissues.…”
Section: Hoxa11‐as Lncrna In Human Cancersmentioning
confidence: 99%
“…Moreover, knockdown of HOXA11‐AS inhibited the proliferation, migration, invasion, tumorigenic as well as the angiogenic capability of NSCLC cells and induced apoptosis. HOXA11‐AS also leads to cell cycle arrest at G0/G1 or G2/M phase 10. In another study, Chen et al concluded that HOXA11‐AS was considerably upregulated in NSCLC tissues, compared with that of normal tissues.…”
Section: Hoxa11‐as Lncrna In Human Cancersmentioning
confidence: 99%
“…13 Studies have found that lncRNA are abnormally expressed in NSCLC, and they regulate the development of NSCLC by stimulating or inhibiting biological processes. 14,15 LncRNA LINC01194 was discovered as a new lncRNA. Studies have confirmed that LINC01194 levels in breast cancer tissues are significantly lower.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, numerous studies have demonstrated that lncRNAs are critically involved in lung cancer progression. Recently, Zhang et al showed that lncRNA HOXA11-AS promotes tumorigenesis in NSCLC through a chick embryo chorioallantoic membrane (CAM) model [10]. Cui et al showed that SNHG1 promotes NSCLC progression via targeting miR-101-3p and modulates Wnt signaling [11] Instead, TFPI2AS1 may function as a tumor suppressor in NSCLC progression by increasing the expression of cyclin D1 and cyclin-dependent kinases 2 (CDK2) [12].…”
Section: Introductionmentioning
confidence: 99%